القيم في برنامج لو كان بيننا دراسة تحليلية - شقوري, عفاف (University of eloued جامعة الوادي, 2016)
الحمد لله رب العالمين والصلاة والسلام على المبعوث رحمة للعالمين نبينا وحبيبنا محمد صل الله عليه وسلم، وبعد: تقوم هذه الدراسة على بيان مدى ترسيخ القيم من خلال برنامج "لو كان بيننا" في موسمه الثاني تحت عنوان "القيم في برنامج لو كان بيننا". والتي أقوم فيها بالإجابة على الإشكالية التالية: ما هي القيم التي تضمنها برنامج لو كان بيننا؟ أ وجبت على هذا الإشكال في خطة مرسومة تنقسم إلى مقدمة، وثلاثة فصول، وخاتمة. الأول: عُني بالإطار المنهجي للدراسة. أ م ا الثاني: فقد تطرقت فيه للجانب النظري وتم فيه التعرف على القيم وخصائصها وأهميتها وطرق اكتسابها...الخ. وأ ما الثالث: خُصص للجانب التطبيقي للدراسة التحليلية التي تم فيها عرض النتائج الخاصة بالمضمون وبالشكل.خاتمة: ذيلت بأهم النتائج الخاصة بالدراسة وأهم التوصيات Praise be to Allah, and prayer and peace be upon the messenger of mercy to the worlds , our beloved Prophet Mouhammad, bless him, and after that, This study is based on the extent of the values consolidation through the program " if it was between us " in its second season under the title " Values in the program if it was between us ". And in which we are answering the following problem question : What are the values contained in the program if it was between us ? And according to the drawn plan, which is divided into three chapters, the first was related to the methodological framework for the study, while the second has singled out the theory side wherein was the identification of values, characteristics and importance and ways it is acquired ... etc. The third, which was allocated to the side of the applied analytical study that display the results related to the content and the form and with the study conclusion, which were appended to the results of the study and some of the recommendations.
ماستر دعوة
Keywords: برنامج,القيم; program, values